2016
DOI: 10.1177/1687814016662228
|View full text |Cite
|
Sign up to set email alerts
|

Relevance feature selection of modal frequency-ambient condition pattern recognition in structural health assessment for reinforced concrete buildings

Abstract: Modal frequency is an important indicator for structural health assessment. Previous studies have shown that this indicator is substantially affected by the fluctuation of ambient conditions, such as temperature and humidity. Therefore, recognizing the pattern between modal frequency and ambient conditions is necessary for reliable long-term structural health assessment. In this article, a novel machine-learning algorithm is proposed to automatically select relevance features in modal frequency-ambient conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Modeling the ambient influence on the structural health indicators is crucial for reliable structural health monitoring (Brownjohn, 2007; Giagopoulos et al., 2019; Kuok & Yuen, 2012; Li, Yi, Ren, Li, & Huo, 2014; Liu, Lu, Yin, & Noori, 2016; Mu, Yuen, & Kuok, 2016). Due to the nature of complex and volatile mechanism, constructing a representative parametric input–output relationship to describe the subtle environmental effects on materials properties and structural behavior under severe wind loading can be a nontrivial task (Catbas, Susoy, & Frangopol, 2008; Kuok & Yuen, 2016; Lam, Zhang, Ni, & Hu, 2017; Lei, Su, & Shen, 2013).…”
Section: Case Studymentioning
confidence: 99%
“…Modeling the ambient influence on the structural health indicators is crucial for reliable structural health monitoring (Brownjohn, 2007; Giagopoulos et al., 2019; Kuok & Yuen, 2012; Li, Yi, Ren, Li, & Huo, 2014; Liu, Lu, Yin, & Noori, 2016; Mu, Yuen, & Kuok, 2016). Due to the nature of complex and volatile mechanism, constructing a representative parametric input–output relationship to describe the subtle environmental effects on materials properties and structural behavior under severe wind loading can be a nontrivial task (Catbas, Susoy, & Frangopol, 2008; Kuok & Yuen, 2016; Lam, Zhang, Ni, & Hu, 2017; Lei, Su, & Shen, 2013).…”
Section: Case Studymentioning
confidence: 99%
“…Temperature is a critical loading factor for structures [ 32 ]. Variation of temperatures in structures significantly influences the material properties (for example, Young’s modulus [ 32 ]), static characteristics (for example, deflection and deformation [ 32 ]), dynamic characteristics (for example, structural frequencies [ 33 , 34 , 35 ], damping ratios and mode shapes [ 36 ]) and boundary conditions [ 37 ]. Temperatures, including ambient air temperature and structural component temperature, of a multi-sensor of a structure are uncertain due to the fact that they are affected by not only the ambient factors, including air temperature variation, solar radiation intensity, humidity and wind speed, but also the complex processes of heat transfer [ 38 ].…”
Section: Illustrative Examplesmentioning
confidence: 99%
“…However, long-term structural health monitoring of in-service infrastructures demonstrated that the structural health indicators are sensitive to varying operating conditions. 8,9,[14][15][16] Inevitable operating interferences, such as temperature and humidity, [17][18][19][20][21] wind velocity, [22][23][24][25] traffic loading, 26,27 and base excitation, 28 can induce significant contributions to the variation of structural health indicators. In order to make reliable judgments of the deterioration of structural integrity, modeling the ambient interferenceinduced variation of the structural health indicators is essential.…”
Section: Introductionmentioning
confidence: 99%